High Fertility, High Infant and Child Mortality And the Tragedy of the Commons in Tanzania - Maghimbi, Sam (Tanzania Journal for Population studies and Development, 2014)
Tanzania has reduced the rates of infant and under-five mortality to below the national goals of 50/1,000 and 70/1,000. However, current rates are still high by international standards, and maternal mortality and fertility rates are high. Tanzania parents have a fatalistic mental attitude towards birth and death. The presence of a commons in child rearing helps to make parents view it rational to add more children to the commons. The existence of the moral economy in subsistence is related to a commons, and has the same impact. The theory of the tragedy of the commons is drawn from Lloyd, and is used to show how parents’ faith in the commons leads to the tragedy of high infant and child mortality. Infant and child mortality is a complex question for parents but their reasoning tends to be fallacious as they answer it with more births and more deaths. The conclusion is that although infant and under-five mortality rates are declining, given the current conditions in Tanzania, parents may continue to attribute false causes to infant and child mortality and many children may continue to be born and die.